Tafsir Fiqhiyah Q.S. Al-Mumtahanah [60]: 8-9 dalam Hukum Mengucapkan ‘Selamat’ pada Perayaan Non-Muslim - Leni Maulida; Ahmad Faisal Kamil Mabarak; Akhmad Dasuki (JOURNAL SAINS STUDENT RESEARCH, 2025)
In a multicultural society, interactions between Muslims and non-Muslims are often debated, including the aspect of congratulating non-Muslims on their religious celebrations. This article analyzes QS. Al-Mumtahanah [60]: 8-9 in the perspective of fiqh interpretation to understand the law of congratulating non-Muslims. This research uses a qualitative method with a library research approach, analyzing books of tafsir and the opinions of scholars of the madhhab. The results of the study show that the majority of contemporary scholars allow congratulations on the condition that they do not contain recognition of the creed of other religions. However, there are also opinions that prohibit it because it is considered a form of tasyabbuh (imitation) and support for non-Muslim beliefs. This study emphasizes that the understanding of Islamic law must consider the principle of tolerance without ignoring the Islamic creed, as explained in Q.S. Al-Mumtahanah [60]: 8-9.